RANCANG BANGUN KOTAK AMAL PINTAR MENGGUNAKAN SENSOR TCS34725 BERBASIS ESP32 DENGAN SISTEM KEAMANAN GPS - Fathan Agil Barra Putra, (2024)
Charity boxes are a medium used to collect money from alms obtained from the community. Charity boxes are often found in places of worship such as mosques. In general, a charity box is just a cube-shaped container with a hole to put money in. With this simple design, of course it creates a number of problems. An example of a common problem is the process of calculating money in a box which can make it difficult for mosque officials in the process of recording finances. Another problem that often arises with conventional charity boxes is the security of the charity box itself, namely cases of charity box theft caused by the box's security system being less than optimal. Therefore, this research carried out the development of a smart charity box innovation concept that is integrated with automation technology. The smart charity box is equipped with an ESP32-based system which can carry out automatic reading and calculation of money as well as a security system in the form of monitoring the location of the charity box in real-time using the TCS34725 color sensor and GPS Module NEO 6M inside. The results of this research are that the smart charity box can work quite well according to the initial planning and hypothesis, namely detecting and recording money and monitoring the location of the charity box.